Late sequelae of osteoarticular infections in pediatric patients: A single-center study. Issue 8 (26th February 2021) - Saad, Lydia; Hupin, Mathilde; Buteau, Chantal; Nault, Marie-Lyne
Abstract : Abstract: To review the orthopedic sequelae of pediatric patients diagnosed with osteoarticular infections (OAIs) and identify significant differences between those with and without sequelae. Medical charts between 2010 and 2016 from a tertiary-care pediatric hospital were reviewed to collect demographic and clinical data for this retrospective case series. The main inclusion criteria were: age (⩽10 years old); absence of sickle cell anemia and immunocompromising disease or medication; a minimum follow-up of 12 months with radiographs; and diagnosis of osteomyelitis of long bones and/or septic arthritis. The following late sequelae were observed and aggregated: osteal deformations that led to limb-length discrepancies (LLD) superior to 5 mm, abnormal articular angulations of more than 5°, and symptomatic chondropathies visible on imaging studies after 1 year. The patients were divided into 2 subgroups: with and without sequelae. Chi-Squared tests were used for categorical variables and Mann–Whitney U tests for continuous data to identify statistically significant differences between the 2 subgroups. Among 401 patients with osteomyelitis and/or septic arthritis, 50 (12.5%) were included (24 girls and 26 boys). There were 36 (72%) cases of osteomyelitis, 8 (16%) cases of septic arthritis, and 6 (12%) cases of combined infection (3 acute/subacute and 3 chronic cases). Five (10%) patients had orthopedic sequelae at the latest follow-up. The total duration of antibiotic treatment ( P = .002), infectious disease follow-up ( P = .002), and the presence of sequestra ( P = .005) were significantly different between subgroups. There were no statistically significant differences between the 2 subgroups for the other variables, but some trends could be discerned. Only 4/50 patients developed a sequestrum, 2 of which were in the orthopedic sequelae subgroup. Furthermore, initial C-reactive protein (CRP) values were higher in the sequelae subgroup, as were the CRP values at hospital discharge. The orthopedic follow-up was also longer in the sequelae subgroup. Finally, the delay between the onset of symptoms and the beginning of antibiotic treatment was longer in the sequelae group. Patients with orthopedic sequelae had a longer antibiotic treatment and infectious disease follow-up, and were more likely to have presented with a sequestrum. Level of evidence: IV – case series.